Habitat Use, Terrestriality and Feeding Behaviour of Javan Slow Lorises in Urban Areas of a Multi-Use Landscape in Indonesia - Laura Karimloo; Marco Campera; Muhammad Ali Imron; Shrey Rakholia; Abhinav Mehta; Katherine Hedger; K.A.I. Nekaris (Land, 2023)
Urban areas are rapidly expanding into natural habitats worldwide. When species are threatened with habitat loss, it is vital to understand how they will respond or adapt to the change in their environment. One primate species threatened by habitat loss is the fully arboreal Javan slow loris (Nycticebus javanicus). This non-leaping species not only relies on canopy continuity but is also subject to capture for illegal wildlife trade, especially in anthropogenic landscapes where they are easier to catch. We examine the use of urban areas by Javan slow lorises in terms of habitat use as well as feeding and terrestriality behaviours in the municipality of Cipaganti in West Java, Indonesia. For this study, we observed Javan slow lorises from May 2018 to April 2020 for two dry periods and two wet periods. We combined home ranges and core areas with a land cover classification of the area to understand the composition of the loris habitat. We also included feeding and terrestriality data to determine the ratio of these activities within each land cover class. We found that approximately half of their territory falls into natural areas (bamboo patches: 45–60%), and the other half is in human land use areas (agriculture, shade gardens, urban areas, and fallow land). Urban areas ranged from 0 to 54% of an individual loris’s habitat, with the proportion of urban land cover being higher in some individuals’ core areas than in their home ranges. Only urban areas showed a variation between periods, with p-values of 0.06 and 0.002 for home ranges and core areas, respectively, showing a significant increase usage during dry periods. Of all feeding observations, 4% occurred in urban areas with nectar being the most common feeding item. We recorded thirteen different food species in urban areas with Calliandra calothrysus being the most frequent. We found that 7% of terrestriality events occurred in urban areas. The findings from this study show that human land use areas cover a significant portion of the Javan slow lorises habitat in this region, further emphasising the need to consider the needs of these Critically Endangered primates when developing natural habitats into those of human managed landscapes. The same principles are true for the large number of species that are able to persist in urban areas in a world increasingly dominated by humans.